Notes on Stigmoderini (Coleoptera, Buprestidae) from Brazil, with the description of a new species of Hiperantha Gistel, 1834, and new distributional records - Pineda, Cristian R.; Barros, Rafael C. (Zootaxa, 2021)
A new species of Hiperantha (Hyperanthoides) is described from northeast Brazil: Hiperantha (Hyperanthoides) pikachu sp. nov. Identification key of the genus Hiperantha is modified to include the new species. We also present a compilation of all species of the genus known from Brazil, including new state records for the following species: H. (s. str.) interrogationis (Klug, 1825), H. (H.) testacea (Fabricius, 1801), H. (s. str.) menetriesii Mannerheim, 1837, H. (s. str.) menetriesii ornaticollis (Gory & Laporte, 1839), H. (s. str.) bella Saunders, 1869 and H. (H.) decorata (Gory, 1841).